Comportamento de navios amarrados no Posto "A" do Porto de Leixões: importância da consideração do carácter irregular da agitação marítima nos estudos em modelo físico - Paulo Rosa Santos (2008)
The interactions between the ship, the mooring system, and the harbor basin are usually complex, with the moored ship having typically a non linear response to the environmental forcing actions. In this context, physical modeling plays an important role.However, in order to obtain reliable results and conclusions, it is essential that the main physical phenomena governing the response of the moored ships are accurately reproduced in the physical model, particularly the wave conditions. The paper intends to enhance the importance of using irregular waves on the studies aiming to evaluate the response of non-linear dynamic systems, which is the case of a ship moored inside a harbor basin. Therefore, the behavior of an oil tanker moored at Berth A of the Leixões Oil Terminal was analyzed under the action of regular and irregular head waves, for different test conditions.